'Willy nilly' doctors, bad patients, and resistant bodies in general public explanations of antimicrobial resistance. Issue 6 (25th May 2020) - Davis, Mark D. M.; Lohm, Davina B.; Whittaker, Andrea; Flowers, Paul
Abstract: Increased public engagement is a feature of policy and communications focussed on the reduction of antimicrobial resistance. Explaining antimicrobial resistance for general publics has proven difficult and they continue to endorse apparently mistaken knowledge, including the conflation of antimicrobial resistance with the notion of the resistant body. We interviewed members of the general public in Melbourne, Australia, to explore explanatory models for antimicrobial resistance and shed light on the persistence of the resistant body assumption and related concepts. In the face of AMR's complexity and the portended antibiotic apocalypse, publics rely on a heavily inscribed understanding of the body defending itself against microbes. Publics also read antibiotic misuse and overuse messages as the responsibility of other patients and medical practitioners, and not themselves. Significantly, the scientific world view that has created expert knowledge about AMR hails publics in ways that discredits them and limits their capacity to take action. Increased engagement with publics will be required to ensure that collaborative and sustainable AMR approaches are fashioned for the future.